A Analysis of E-Samsat Implementation in Increasing Motor Vehicle Tax Revenue at UPTD PPD Samsat Maid Talaud - Lalombombuida, Yosua; Walandouw, Stanley Kho; Mintalangi, Syermi S. E. (Universitas Sam Ratulangi, 2025)
Taxes are mandatory contributions paid by individuals or entities to the state, which are used to finance various development programs and public services. This study aims to analyze whether the application of e-samsat superior services has been effective in increasing motor vehicle tax revenue at UPTD PPD Samsat Maid Talaud. By utilizing information technology, e-samsat is expected to make it easier for taxpayers to make tax payments online, thereby increasing public tax compliance. The method used in this research is descriptive analysis, which includes data collection through interviews, documentation, and observation. The results showed that the implementation of e-samsat superior services has had a positive impact on increasing motor vehicle tax revenue, although there are still challenges in socialization and public understanding of this system. This research is expected to contribute to the development of science in the field of taxation and provide practical input for UPTD PPD Samsat Maid Talaud in improving the effectiveness of the tax collection system.